(untitled) (Research, Society and Development, 2022)
Objective: to analyze the findings available in the literature about bioethical conflicts experienced by women during the birth context. Methods: This is an integrative review research, in which a search was performed in the following databases: Medical Literature Analysis and Retrieval System Online (MEDLINE) via PubMed, Latin American and Caribbean Literature on Health Sciences (LILACS) and Database in Nursing (BDENF), the last two being via the Virtual Health Library (VHL). The inclusion criteria were articles in the languages- Portuguese, English and Spanish, and time frame in the last ten years. Results: After searching and analyzing the articles, three articles were selected that made up the sample of this research. In these, the bioethical conflicts of Autonomy were identified; Beneficiency and Non-maleficence in perinatal care. Conclusion: The bioethical principle that is most in conflict in this context is that of Autonomy, followed by beneficence and non-maleficence.